Zinc ribbon domain containing 1 protein: modulator of multidrug resistance, tumorigenesis and cell cycle - Hong, L.; Han, Y.; Chen, Z.; Zhang, X.; Xia, L.; Han, Z.; Lu, Y.; Jin, H.; Song, J.; Qiao, T.; Fan, D. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
Zinc ribbon domain containing 1 (ZNRD1) gene encoding a protein consisting of two zinc ribbon domains was recently cloned from the human HLA locus. So far, ZNRD1 has been found implicated in transcription regulation and might play potential roles in mediating several biological processes, including multidrug resistance, tumorigenesis and cell cycle. This article reviewed these recent findings and provided additional information to support the role of ZNRD1 gene as a novel candidate DNA damage repair related gene. Ген ZNRD1, кодирующий белок с цинксвязывающим доменом, клонирован из  HLA‑A локуса. Показано, что ZNRD1 принимает участие в регуляции транскрипции и, возможно, в целом ряде биологических процессов, в том числе множественной устойчивости к лекарственным препаратам, онкогенезе и регуляции клеточного цикла. В обзоре обсуждены последние результаты в этой области и приведены данные о роли ZNRD1 в процессах репарации ДНК.